2015
DOI: 10.1016/j.jnucmat.2015.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of Eurofer-97 and Eurofer-ODS steels before and after multi-beam ion irradiations at JANNUS Saclay facility

Abstract: a b s t r a c t RAFM steels such as Eurofer-97 and Eurofer-ODS are potential structural materials for future fusion reactors. In order to study their resistance to the high energy neutrons they will be subjected to in this context, we have irradiated these materials in single-, dual-and triple-beam mode to 26 dpa at 400 C. In single-beam mode (Fe ions only), both materials resist swelling but dislocation loops form. For dual-(Fe and He ions) and triple-beam (Fe, He and H) modes, the same dislocation loop micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 40 publications
(49 reference statements)
1
28
1
Order By: Relevance
“…However, in contrast to the dominating nucleation at dislocations and grain boundaries for neutrons at 450 C, we interprete the observed coexistence in the case of ions at 500 C as an early stage of the tendency for heterogeneous nucleation with rising irradiation temperature. Therefore, we indicate a temperature shift larger than 50 C in agreement with reference [22].…”
Section: Tem-analysis Of the Helium Bubble Distributionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, in contrast to the dominating nucleation at dislocations and grain boundaries for neutrons at 450 C, we interprete the observed coexistence in the case of ions at 500 C as an early stage of the tendency for heterogeneous nucleation with rising irradiation temperature. Therefore, we indicate a temperature shift larger than 50 C in agreement with reference [22].…”
Section: Tem-analysis Of the Helium Bubble Distributionsupporting
confidence: 92%
“…In model alloys dislocation loops caused a spatially heterogeneous distribution of bubbles [34,35] due to a preferential bubble formation at the loops. Nevertheless, the latter was experimentally not observed in the present study even at an elevated irradiation temperature of 500 C as well as in other studies on EUROFER97 [6,22,23].…”
Section: Kinetic Rate Modelcontrasting
confidence: 70%
See 2 more Smart Citations
“…It was APT study that revealed considerable changes in nanoclusters in the neutron irradiated steel to 32 dpa at 330 °C. In ODS Eurofer irradiated with heavy ions at low temperatures (RT, 300 °C and 400 °C), dislocation loops were observed [23,29]. TEM study also showed an increase in density of small (< 5 nm) oxide particles [23].…”
Section: Apt Study Of Irradiated Samples Of Ods Eurofermentioning
confidence: 93%